Research on Modern Marine Environmental Governance in China: Subject Identification, Structural Characteristics, and Operational Mechanisms - Chen, Qi; Yu, Huijuan; Wang, Yezhi (International journal of environmental research and public health, 2021)
Under the guidance of modern environmental governance concepts, there have been profound changes in the subject, structure, and operational mechanism of the modern marine environmental governance in China. This paper first classifies the subjects of modern marine environmental governance in China, as well as their relationships; analyses the structural characteristics from the three levels of rights, society, and region; explores the operational mechanism; and builds the framework of the modern marine environmental governance system in China. Both the central and local governments act as the leaders of the modern marine environmental governance system in China, and there have been many new changes in their relationships. On the one hand, the interest and goals of the central and local governments have gradually converged under the pressure system. On the other hand, local governments follow the principles of comprehensive governance regarding the coastline and collaborative cooperation is gradually beginning to occur. Different governance subjects are interrelated and intertwined to form a complete modern marine environmental governance structure, which includes the following three levels: the governmental power structure; the social structure, which involves collaboration between multiple entities; and the regional structure, which involves land-sea coordination in environmental governance. These structures each play their parts in the overall process of the marine environmental governance’s institutional arrangements, process coordination, and feedback adjustments and ultimately constitute a dynamic and complete modern marine environmental governance operational system.